Meningkatkan Keterampilan Berbicara Siswa Kelas I Melalui Penggunaan Media Gambar Seri - Tana Tana (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
Based on initial observation, it was known that the first grade students at SDN 08 IV Koto Aur Malintang were not confident to  speak in front of class because of feeling shy and afraid. It was caused by learning that focus only on reading and writing skill. Meanwhile, speaking skill had not been concerned yet. This research was aimed to improve the speaking skill of the first grade students at I SDN 08 IV Koto Aur Malintang Kabupaten Padang Pariaman by using media of serial pictures. Data of research were obtained through observing these following aspects: (1) courageous in telling story; (2) fluency in telling story; (3) appropriateness between story and serial pictures; and (4) pronunciation and intonation. Data of research were analyzed qualitatively. Researcher set the mean percentage of four aspects of speaking skill as 80%. In cycle I, the mean percentage of four aspects of speaking skill is 73,8%. Meanwhile, in cycle II, the mean percentage of four aspects of speaking skill is 82,5%. The research result shows that the use of serial pictures can improve the speaking skill of the first grade students at I SDN 08 IV Koto Aur Malintang Kabupaten Padang Pariaman.